Non-linear relationship between platelet count and 28-day mortality in critically ill patients with infective endocarditis: a retrospective cohort study from MIMIC IV database - Yingxiu Huang; Ting Ao; Peng Zhen; Ming Hu (Frontiers in Cardiovascular Medicine)
BackgroundThe relationship between platelet count and 28-day mortality in critically ill patients with infective endocarditis (IE) is currently not well established.ObjectiveThis study aims to investigate the impact of platelet count on 28-day mortality in critically ill patients with infective endocarditis.MethodsA retrospective cohort study was conducted involving 450 participants diagnosed with infective endocarditis and admitted to intensive care units (ICU). Vital signs, laboratory parameters and comorbidity were collected for all participants to analyze the association between platelet count and 28-day mortality. In order to assess the independent association between platelet count and 28-day mortality, we employed multivariable cox hazard regression analyses and smooth curve fitting. A further analysis was conducted using a two-piecewise linear regression model to examine the nonlinear association between platelet count and in-hospital mortality.ResultsA total of 450 critically ill patients with infective endocarditis were included in the study. The mean age was 57.4 years, and 64.2% were male. The overall 28-day mortality rate was 20%. A non-linear relationship was observed between platelet count and 28-day mortality. Two different slopes were identified, with correlations between platelet count and 28-day mortality in patients with IE differing significantly below and above the inflection point, which was approximately 141 K/µl. On the left side of the inflection point, the hazard ratio was 0.990 (hazard ratio: 0.990, 95% confidence interval: 0.982–0.997, p = 0.006). However, on the right side of the inflection point, the hazard ratio increased marginally to 1.0004 (HR: 1.0004, 95% CI: 0.997–1.004, p = 0.825). Notably, the association lacked statistical significance on the right side of the inflection point.ConclusionA nonlinear association between platelet count and 28-day mortality was observed in critically ill patients with infective endocarditis. The optimal platelet count associated with the lowest risk of 28-day mortality was above 141 k/µl.